The Correlation of Social Support and Fear of Breast Cancer among Women in Northeast of Iran: A Cross-Sectional Study - Hassan Joulaei; Mohammad Hossein Delshad; Fatemeh Pourhaji (Shiraz University of Medical Sciences, 2023)
Background: Breast cancer (BC) is the most commonly diagnosed cancer worldwide. Screeningprograms are the most common prevention methods. Perceived social support and fear are twoimportant factors affecting women's participation in breast cancer screening. This study aimed todetermine the relationship between fear of BC and perceived social support among women in TorbatHeydarieh, northeast of Iran.Methods: This study is an online cross-sectional survey that was conducted on 352 women inTorbat Heydarieh city of Northeast Iran, from October 26th, 2021 to December 26th, 2022. Alongwith collecting sociodemographic characteristics, the Breast Cancer Fear Scale (BCFS), and theMultidimensional Scale of Perceived Social Support were electronically administered to participants.Data were analyzed through SPSS software version 25, using independent samples t-tests, one-wayanalysis, Pearson's correlation coefficient, and multiple linear regression models. The statisticalsignificance level was set at P<0.05.Results: The mean score for the BCFS was 20.67±1.03 which was in the moderate range for the totalscore of 40. Assessment of perceived social support indicated a moderate level of perceived supportfor all dimensions. Also, a significant correlation was found between the women's BCFS scores andperceived social support (r=-0.29, P<0.001).Conclusion: We found that there was a negative statistically significant correlation between the BCFand social support. Therefore, this study suggests that healthcare providers pay attention to thesefactors. Moreover, further research is needed to explore the long-term effects of BCF due to low socialsupport.